In Praise of Hedgehogs: Alfred North Whitehead's Critique of Hume - Lincoln, Larkin John V. (My University, 1977)
This essay presents a particular perspective into Alfred North Whitehead's critique of David Hume's philosophy of experience. The first section sets forth the problem which Whitehead saw in Hume's philosophy: the problem that were one to consistently hold Hume's position one would be reduced to what George Santayana calls the 'solipsism of the present moment.' The section section concerns Whitehead's understanding of the cause of Hume's problem, abstraction. Section three considers Hume's particular brand of abstraction, sensationalism, and its relation to visual experience. Section four deals with the rudiments of the Whiteheadian solution of Hume's problem. A brief conclusion attempts to put Whitehead's critique into perspective and suggest further inquiries.
Keywords: Philosophy; Philosophy